OBTAINING A HIGH-PERFORMANCE SEMICONDUCTOR USING A FLOW OF NEUTRONS (Multidisciplinary Journal of Science and Technology, 2026)
In this article, we will consider the process of obtaining high-impedance semiconductor materials using a neutron flux and the study of their electrical properties. In particular, we will analyze such important parameters as electrical resistance, charge carrier concentration and their mobility in semiconductors. We will determine that nuclear reactions occurring in the semiconductor crystal lattice as a result of neutron irradiation lead to a change in the electrical properties of the material. The results of the research show that the possibilities of obtaining high-impedance semiconductors and their application in modern electronic devices have been further expanded.